-2x - 6xy - 3y +7x.....need help bc tomorrow have a test.
2 answers:
Step-by-step explanation:
-2x - 6xy - 3y + 7x <em>combine like terms</em>
= (-2x + 7x) - 6xy - 3y
= 5x - 6xy - 3y
Hey there! We will Combine Like Terns for this one.
= −2x + −6xy + −3y + 7x
= (−6xy) + (−2x + 7x) + (−3y)
=−6xy + 5x + −3y
You might be interested in
Answer:
82
Step-by-step explanation:
opposite angles in a cyclic quadrilateral are supplimentary
X is obviously 1
1x2=2
Entao...(So...)
Please mark as brainliest
Answer:
6/5
Step-by-step explanation:
Answer:10 Tablets must be taken
Step-by-step explanation:
V=5
5×2=10
1 minute = 60 seconds
300 seconds / 60 seconds = 5 minutes